Periprocedural Thromboembolic Events Associated with Angioplasty and Stenting of the Extra- and Intracranial Carotid Artery Assessed by Neurological Status and Diffusion-Weighted Magnetic Resonance Imaging (DWI). (22nd October 2012) - Ahlhelm, Frank; Lieb, Johanna; Ulmer, Stefan; Ahlhelm, Dirk; Reith, Wolfgang
Abstract : Objective . The purpose of this study was to determine the frequency of thromboembolic events associated with angioplasty and stenting of the carotid artery with special regard to extra- or intracranial localization of stenosis. Methods . Twenty patients with symptomatic intracranial or extracranial internal carotid artery stenosis were treated with stenting and/or angioplasty. In 4 patients stenting was technically not feasible (all in the group with intracranial stenosis). All patients underwent diffusion-weighted imaging (DWI) and neurological examination within 48 hours before and after the procedure to detect periprocedural thrombembolic events. Results . Extracranial carotid angioplasty and stenting (eCAS) was technically feasible and successfull without procedure-related neurological complications in all cases. Intracranial stenting (iCAS) was not feasible in four cases including one patient with a fateful course. Concerning the restoration of the vessel diameter intracranial stenting was not as successful as eCAS, but more effective than balloon angioplasty alone. Incidence of thrombembolic events assessed by DWI was low. The detected periprocedural thrombembolic events were small and clinically silent. Conclusion . The risk of thromboembolic events during the endovascular treatment of symptomatic carotid artery stenosis was rather low for intra- and extracranial stenosis of the ICA in our patient sample, but one fatal course was observed.